Determination of the coefficient of rolling friction of irregularly shaped maize particles by using discrete element method - Shi, Linrong; Zhao, Wuyun; Sun, Bugong; Sun, Wei (International Journal of Agricultural and Biological Engineering, 2020)
The coefficient of rolling friction is a foundation parameter for conducting particles simulation, however, which of irregularly shaped maize seeds is difficult to measure. Furthermore, the coefficient of rolling friction between the simulation particles and the actual seeds is inconsistent due to the shaped difference of model and different position of gravity center. This paper use two methods to determinate the coefficient of rolling friction based on discrete element method (DEM) and physical experiments. Three types of maize models from five different shaped maize samples (including horse-tooth shape, spherical cone shape, spherical shape, oblate shape, irregular shape) were developed with the help of slice modeling and 3D modeling technology. Aluminum cylinder container is used to arrange the simulation experiments of angle of repose with taking the coefficient of rolling friction as independent variables and the simulation angle of repose as target values. After predicting detailed the coefficient of rolling friction (including horse-tooth shape, spherical cone shape, spherical shape, between horse-tooth shape and spherical cone shape, between horse-tooth shape and spherical shape, between spherical shape and spherical cone shape maize models), and forecasting a unified the coefficient of rolling friction among horse-tooth shape, spherical cone shape and spherical shape maize models, two types of materials (aluminum cylinder container and organic glass container) were used to validate the difference the angle of repose between the simulation maize models and actual maize seeds. Results show the relative error of the angle of repose between the maize models controlled by the coefficient of rolling friction through the detailed method and the actual maize seeds is 0.22%, 0.33% in aluminum cylinder, organic glass container, respectively. The relative error of the angle of repose between the simulation maize models controlled by the coefficient of rolling friction through the united method and actual maize seeds is 2.47%, 2.97% in aluminum cylinder, organic glass container, respectively. Although the difference of the angle of repose between two method is smaller, the detailed method is better. Moreover, From the accumulation process of the angle of repose we found that the difference on the contacts number between maize models and bottom plate, the change curve of the rotational kinetic energy, the potential energy of maize models controlled by the coefficient of rolling friction through the detailed and the united method are evidently. We can choose a better method to predict the coefficient of rolling friction of maize seeds according to the application situation and investigation objective of irregular maize seeds. The results can provide a theoretical basis for designing and optimizing the structure of the seed-metering machine with DEM. Keywords: coefficient of rolling friction, maize, irregularly shaped model, angle of repose, discrete element method DOI: 10.25165/j.ijabe.20201302.4688 Citation: Shi L R, Zhao W Y, Sun B G, Sun W. Determination of the coefficient of rolling friction of irregularly shaped maize particles by using discrete element method. Int J Agric & Biol Eng, 2020; 13(2): 15–25.